Education Values Based On The Thinking Of K.H. Choer Affandi And Their Relevance To The Modern Education - Hidayat, Tatang (State Islamic Institute of Madura, 2019)
The existence of pesantrens in the Indonesian archipelago, such as Pondok Pesantren Miftahul Huda Manonjaya, Tasikmalaya is a major transformation for the development of the national education system. This present study aims at investigating the educational values based on the thinking of K.H. Choer Affandi and their relevance to the modern education. This study employed a qualitative approach and descriptive method. In this present study, the researcher acted as the main instrument. The data collection techniques employed in this study covered interviews, observation, and documentation studies. Based on the results of the study, it showed that K.H Choer Affandi was a salafiyah Islamic scholar born from a knowledgeable, fighter, and noble family. Coming from the aforementioned reason, he was eventually active in education realms and movements. Educational values of K.H. Choer Affandi consist of iman and taqwa values, leadership, independence, discipline, honesty, persistence (istiqomah), courage (syaja'ah), intelligence and simplicity values (tawaḍu) Therefore, the educational values of K.H. Choer Affandi is still relevant in modern education today, because modern education has lost its essential meaning, revoked from the roots of the values of education itself.Keywords: Education Values, K.H. Choer Affandi, Modern Education, Pondok Pesantren Miftahul Huda